1990
DOI: 10.1111/j.1570-7458.1990.tb01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative value of four arcelin variants in the development of dry bean lines resistant to the Mexican bean weevil

Abstract: Wild Phaseolus vulgaris L. accessions containing arcelin codominant alleles 1 through 5 were reconfirmed and characterized for resistance to the Mexican bean weevil, Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae). Accession G 02771 (arcelin 5) had the highest level of antibiosis resistance, followed by G 12952 (arcelin 4), G 12882 (arcelin 1) and G 12866 (arcelin 2). Arcelin 3 accessions conferred the lowest levels of resistance. As the presence of arcelin is inherited as a single dominant gene, a bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
9

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 9 publications
4
67
0
9
Order By: Relevance
“…Each arcelin variant is composed of several polypeptides presumably encoded by a family of different genes (Hartweck, Vogelzang, & Osborn, 1991). The importance of arcelin in the present perspective is its insecticidal property and in particular their inhibitory activity on larval development in stored product pests (Cardona, Kornegay, Posso, Morales, & Ramirez, 1990;Janarthanan & Suresh, 2003;Janarthanan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Each arcelin variant is composed of several polypeptides presumably encoded by a family of different genes (Hartweck, Vogelzang, & Osborn, 1991). The importance of arcelin in the present perspective is its insecticidal property and in particular their inhibitory activity on larval development in stored product pests (Cardona, Kornegay, Posso, Morales, & Ramirez, 1990;Janarthanan & Suresh, 2003;Janarthanan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Certain wild accessions of common beans are resistant to Z. subfasciatus and several groups have introgressed this resistance into cultivars by selecting for arcelin (Schoonhoven et al, 1983;Osborn et al, 1988;Cardona et al, 1990). Arcelin is not a single protein, but is classified as six electrophoretic variants (Osborn et al, 1986;Suzuki et al, 1995).…”
Section: Why Does Aai Not Play a Role In The Resistance Of Introgressmentioning
confidence: 99%
“…of this protein family, arcelin, is found only in wild accessions of the common bean, and the introgression of the arcelin gene(s) yields varieties that are resistant to Z. subfasciatus (Andreas et al, 1986;Osborn et al, 1986;Cardona et al, 1990). It appears that the larvae of A. obfectus and Z .…”
mentioning
confidence: 99%
“…Although phytohemagglutinins from P. vulgaris did not provide protection to P. vulgaris predators, they did provide protection against seed-feeding pests of other Phaseolus species. Osborn et al (18) showed that arcelin-1 protected seeds against P. vulgaris pests and recently the four arcelin variants were found to be associated with different levels and types of resistance to the Mexican bean weevil or the common bean weevil (3,8). Characterization of arcelin variants and comparisons to each other as well as to PHA may aid in understanding specific host-pest interactions, thereby enabling plant breeders to plan an effective strategy to control bruchid pests.…”
mentioning
confidence: 99%